A chronological review of the development of elite sport policy in South Korea - Park, J.-W.; Lim, S. (Asia Pacific Journal of Sport and Social Science, 2016)
This article provides a chronological review of the development of elite sport policy in South Korea. It seeks to review the development of the elite sport policy and system in relation to the broader social and political context of South Korea by framing it in four time periods: 1961-1979, 1980-1992, 1993-2002 and 2003 onwards. The paper reveals the four key features of Korean elite sport development in terms of policy. The first of these is the country`s aim of maintaining a position in the top 10 of the Olympic medal standing which has been a key criterion for the success or failure of the nation`s elite sporting performance since the 1984 LA Olympics. The second notable feature of Korean elite sport development is that the country`s good performance and achievements in the global sporting competitions have their roots in the elite sport-oriented policy of the previous military-based regimes. The political drive for the development of an elite sport policy emphasis on success was made possible due to the ideological and political use of sport. The third noticeable feature of the Korean elite sport development is the role of big businesses (so-called `Chaebol`) in the glory of elite sporting success. The final significant feature of Korean elite development relates to the signs of change in recent years, which have witnessed a growing awareness of the negative aspects (and structural problems) of Korean elite sport development associated with achieving elite sporting success at all costs